Administrative Turnover in Kansas Rural School Districts: 1978-1984 - Alfred P. Wilson; John M. Heim (Journal of Research in Rural Education, 1985)
Kansas is typical of most people's concept of rural America. It has a population of less than two and onehalf million people spread over 81,000 square miles, making Kansas the 32nd largest in population and the thirteenth largest in total land area of the fifty states. Few states have fewer people than Kansas and many large cities have larger populations than the state.